Inflation and Stock Market Performance in a Developing Country: The Bangladesh Outlook - Md. Touhidul Islam (Economics, Business, Accounting & Society Review, 2024)
This research adds empirical evidence from a developing country to the research topic: how does inflation impact stock market performance? Stock market performance is measured by the all-stock index (DSEX) of the premiere bourse in Bangladesh – Dhaka Stock Exchange (DSE). A multivariate regression model is used to investigate the relationship between inflation and stock market performance in Bangladesh. Evidence from previous literature exists of positive and negative relationships between these two variables. By examining monthly data from June, 2012 until March, 2024. It is found that inflation is negatively related to stock market performance in Bangladesh. The research paper also uses three control variables: private sector credit growth, remittance, and exchange rate. Two of them are negatively related to the stock market index, and the other is positively related.